Analysis of Antibiotic Therapy Accuracy and Drug Interaction in Pneumonia Inpatients at The Islamic Hospital Jakarta Cempaka Putih - Khairani, Sondang; Manninda, Reise; Ariani, Lusiana; Iskandar, Benni; Hidayati, Nabila Nur (Sciences of Pharmacy, 2025)
Polypharmacy may increase the risk of drug interactions affecting toxicity and therapeutic efficacy in pneumonia patients. This study aimed to analyse evaluation of pneumonia management, polypharmacy, relationship between polypharmacy and occurrence of drug-drug interactions, and relationship between drug-drug interactions and length of hospital stay of pneumonia patients. The study design used a quantitative descriptive approach with cross-sectional and retrospective data collection and a total sample of 113 samples that met the criteria. Analyses were performed using Spearman's rho correlation test to assess the association of polypharmacy with drug interactions, and the association of drug interactions with length of hospital stay. Medication accuracy was measured using PDPI (The Indonesian Lung Doctors Assosiaciation) guidelines, drug interactions using drugs.com and/or Medscape.com. Results showed 59.29% of patients were female, with the majority aged over 65 (55.65%). Most patients (91.15%) paid with BPJS, 62.61% were hospitalised for 1-5 days and 81.74% had comorbidities. Treatment accuracy in this study was 49.56%. 106 drug interactions were identified in a total of 226 cases. 66% of the interactions were pharmacodynamic with moderate severity (79%), such as the interaction between combivent and ondansetron. Mild pharmacokinetic interactions were common, especially between ranitidine and paracetamol (22 cases). There is a correlation between polypharmacy and drug interactions with a p-value 0.000 and there is a correlation between the number of drug interactions and length of hospitalisation with p-value 0.000. Conclusion of this study is polypharmacy increases the risk of drug interactions and affects the length of hospital stay in pneumonia patients.